Ewolucja wspólnej polityki rolnej ukierunkowanej na zrównoważone rolnictwo - Łuczka-Bakuła, Władysława (Evolution of common agricultural policy directed towards sustainable agriculture, 2007)
The main premises, directions and instruments of Common Agricultural Policy reform, aiming towards environmental goals realization, beginning from MacSharry reform, and closing with the Luxembourg Agreement were presented in the elaboration. Concluding it was recognised that former Common Agricultural Policy reforms violate neither its essence, nor its bases. It is still directed on highly-intensive farms support, which indicates the need of continuation of the policy reorientation process in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 334-345